UDC and e-Service Delivery at Local Government Level in Bangladesh: A Framework for e-Government (Bangladesh Journal of Public Administration, 2020)
This is the age of Information and Communication Technology (ICT) which has brought change by being an integral part of governmental service delivery of the twenty-first century. Public service delivery is a great concern for governments. The present government of Bangladesh has realized this fact of ICT and has introduced ICT based Union Digital Centre (UDC), district and upazila web portals to provide quicker and smoother services to the people for creating “Digital Bangladesh”. The main focus of this study is to bring citizens under the whole e-governance system. ICT based UDCs are the main actors for this purpose.The present government has set up 4547 service centres at every Union level (the lowest tier of Local Government) which is known as Union Digital Centre (UDC). ICT based UDCs providetime and cost effective some sorts of off-line and online door step services to the rural people.The broad objective of this study is to make an e-government framework at the local government level in Bangladesh by providing e-services through UDC. The specific objectives are: To find out the role of UDC in public service delivery at the local government level in Bangladesh; and to know the effectiveness of UDC in promoting e-government by delivering e-services to the people. This study has attempted a qualitative research approach to obtain its objectives.